2011
DOI: 10.3917/spub.113.0195
|View full text |Cite
|
Sign up to set email alerts
|

L'intoxication par les pesticides chez l'enfant au Maroc : profil épidémiologique et aspects pronostiques (1990-2008)

Abstract: Acute pesticide poisoning among children is a reality in Morocco. Preventive measures may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…When we exclude the unintentional cases among children, the mean age among cases of self-harm compared with unintentional poisonings is lower as most often found in other studies. 10,22,23 Female cases were younger in both the urban and rural data, but the difference was only significant for female urban cases of self-harm, whereas female rural cases of self-harm were slightly older than men. Most other studies found female self-harm cases being younger than men.…”
Section: Discussionmentioning
confidence: 91%
“…When we exclude the unintentional cases among children, the mean age among cases of self-harm compared with unintentional poisonings is lower as most often found in other studies. 10,22,23 Female cases were younger in both the urban and rural data, but the difference was only significant for female urban cases of self-harm, whereas female rural cases of self-harm were slightly older than men. Most other studies found female self-harm cases being younger than men.…”
Section: Discussionmentioning
confidence: 91%
“…Females may voluntarily intoxicate themselves as a desperate attempt to drown their sorrows, commit abortions or suicide. Females are often the most vulnerable group to suicide attempts (Achour et al, 2011). Above all, accidental poisoning was more frequent; a few cases were intentional, contrary to the findings of a study carried out in Hospitals of the Mazandaran University of Medical Sciences where intentional poisoning was quite frequent and reached 51.6% (Saravi, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…The age group 16-30 years old was most affected. Similar studies have confirmed the vulnerability of young people to poisons (Achour et al, 2011;Arulmurugan et al, 2017;Chen et al, 2010;Gupta et al, 1998;Oreby et al, 2016). Nevertheless, in a study carried out between 1999 and 2008 in Taiwan, aged males above 65 years old were the most affected group with medicinal drug poisoning (Chien et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…In our country, organophosphate is the most common product involved in child poisoning with industrial products [18], a substance for which, unlike triclopyr and other herbicides, an antidote and management guidelines are available [19].…”
Section: Discussionmentioning
confidence: 99%